2011
DOI: 10.1002/mame.201000350
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for the Reinforcement of UV‐Cured Coatings via Sol‐Gel Photopolymerization

Abstract: A difunctional methacrylate oligomer was mixed with a variable amount of a MAPTMS precursor in the presence of both a radical and a cationic photoinitiator. The simultaneous photolysis of both photosensitive molecules upon UV irradiation allowed the single‐step generation of a type‐II polymethacrylate/polysiloxane nanocomposite film. Methacrylate and methoxysilyl conversions during irradiation were efficiently monitored by FTIR spectroscopy. The inorganic structure of the resulting silica‐based hybrid films wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…These precursors, which have to be thermally or photo-chemically cured leads to an organic network, tangled up to the inorganic one. Close to this approach, it is also reported that the addition of pure organic monomers to the network former performs a double reticulation and creates a convolution of both O/I networks [4,10,[22][23][24][25]. In any case, sol-gel process mastery is primordial to prepare a stable sol, able to be deposited and reticulated in a three dimensions O/I hybrid network.…”
Section: Introductionmentioning
confidence: 90%
“…These precursors, which have to be thermally or photo-chemically cured leads to an organic network, tangled up to the inorganic one. Close to this approach, it is also reported that the addition of pure organic monomers to the network former performs a double reticulation and creates a convolution of both O/I networks [4,10,[22][23][24][25]. In any case, sol-gel process mastery is primordial to prepare a stable sol, able to be deposited and reticulated in a three dimensions O/I hybrid network.…”
Section: Introductionmentioning
confidence: 90%
“…When the hybrid methacrylate-silane precursor is incorporated into the dimethacrylate monomer and exposed to UV irradiation in the presence of both a radical and a cationic photoinitiator, the crosslinking of both the organic and the inorganic networks occurs in a single-step producing an hybrid nanocomposite coating [10][11] . The radical photoinitiator will initiate the photopolymerization of the methacrylate groups while cationic photoinitiator will catalyze the sol-gel process with hydrolysis of the methoxysilane groups (R-SiOCH 3 + H 2 O ' R-SiOH + CH 3 OH) followed by polycondensation reactions.…”
Section: Hybrid Organic Inorganic Network Exhibiting Enhanced Thermomentioning
confidence: 99%
“…They clearly showed that both organic and inorganic parts reacted upon UV exposure. In addition, 29 Si solid state NMR was implemented to characterize the inorganic network 11 . These experiments confirmed that protonic acids generated by the photolysis of the cationic photoinitiator were able to induce the sol-gel condensation in addition to hydrolysis reactions previously evidenced with FT-IR.…”
Section: Hybrid Organic Inorganic Network Exhibiting Enhanced Thermomentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility in order to improve the surface properties of a light emitting organic coating could be using hybrid organic/inorganic materials as host matrices that already posses improved surface properties. Taking into account the wide literature available in developing advanced organic/inorganic hybrid polymeric films,19–31 in this paper we followed the strategy to create silica nanodomains directly in the matrix involving a series of hydrolysis and condensation reactions of metal alkoxide precursor dispersed in the initial formulation 32. The use of an appropriate coupling agent allows a stronger interaction between the polymer matrix and the inorganic component, leading to a material in which the inorganic phase is chemically bonded to the organic phase (hybrid material) 33.…”
Section: Introductionmentioning
confidence: 99%